Printed books 1468-1700 in the Library of the Hispanic Society of America. A listing by Clara Louisa Penney. The Hispanic Society of America, New York, 1965; xlii + 614 pp. + 4 hojas de láminas. / The Hispanic Society of America. An album of selected bookbindings, by Clara Louisa Penney. New York, 1967; xv + 18 pp. [con 3 hojas de láms. intercaladas, una de ellas en color] + láms. I-LX. - Alatorre, Antonio (El Colegio de México, 1970)
Se reseñaron los libros: Printed books 1468-1700 in the Library of the Hispanic Society of America. A listing by Clara Louisa Penney, y The Hispanic Society of America. An album of selected bookbindings, by Clara Louisa Penney.